Combining the strategies of using focused written corrective feedback: a study with upper-elementary Chilean EFL learners - Pamela Andrea Saavedra Jeldres; Mónica Campos Espinoza (Colombian Applied Linguistics Journal, 2018)
This report describes a mixed-methods study comparing the writing performance of 60 EFL students in three intact groups during their first semester of an English undergraduate program at a university in the South of Chile. Three types of focused, indirect written corrective feedback were used: Group 1, coding (n = 23); Group 2, brief grammatical explanation (n = 22); and Group 3, underlining (n = 15). Feedback was given on five targeted linguistic categories. A pre-test was applied before the 16-week treatment took place, as well as a post-test. Students received explicit grammar training and knowledge of genres. Multiple-drafting was used in a writing-portfolio-based class that allowed them to see their progress over time. Frequency and standard deviation of errors (viz., subject omission, spelling, subject verb agreement, capital letters and indefinite articles) were calculated for the pre- and post-test. Qualitative data were collected from group semi-structured interviews and were analyzed using content analysis. Results show that two out of the five linguistic categories (use of capital letters and indefinite articles) improved significantly in terms of accuracy, and there are differences among types of feedback. Interviews indicated that students were satisfied with the writing portfolio system because it allowed them to keep track of their progress. In addition, they valued the systematic feedback and had a positive attitude towards multiple drafting and the writing process approach.